An interaction framework for multiagent systems - Miller, Matthew James (Kansas State University, 2012)
A multiagent system is a system that is composed of multiple autonomous agents. Au- tonomous agents are given the right and the responsibility to make decisions based on their perceptions and goals. Agents are also constrained by their capabilities, the environment and the system with which they reside. An agent within the system may need to coordinate with another agent in the system. This coordination may allow the agent to give updates from sensor readings, communicate updated map information or allow the agent to work on a cooperative task such as lifting an object. To coordinate agents must be able to communicate with one another. To communicate agents must have a communication medium. The medium is the conduit through which the information flows. Additionally there must be a set of rules to govern which agent talks at what time. This set of rules is called a communication protocol. To effectively and efficiently communicate all agents participating in the communication must be using compatible protocols. Robotic agents can be placed in diverse environment and there are multiple avenues for communication failure. Current multiagent systems use fixed communication protocols to allow agents to interact with one another. Using fixed protocols in an error prone environ- ment can lead to a high rate of system failure. To address these issues, I propose that a formal framework for interaction be defined. The framework should allow agents to choose new interaction protocols when the current protocol they are using fails. A formal framework allows automated tools to reason over the possible choices of interaction protocols. The tools can enumerate the protocols that will allow the agent to achieve its desired goal.
Keywords: Multiagent; Interaction; Adaptation; Robustness; Computer Science (0984)